Malaria parasites regulate intra-erythrocytic development duration via serpentine receptor 10 to coordinate with host rhythms - Amit K. Subudhi (Nature Portfolio, 2020)
The mechanism underlying periodicity of Plasmodium’s intra-erythrocytic developmental cycle (IDC) is unclear. Here, Subudhi et al. show that serpentine receptor 10 (SR10) plays a role in regulating the schedule of the IDC in line with the timing of host daily rhythms.